2022
DOI: 10.1172/jci.insight.140738
|View full text |Cite
|
Sign up to set email alerts
|

Commensal oral microbiota induces osteoimmunomodulatory effects separate from systemic microbiome in mice

Abstract: Commensal microbes critically regulate skeletal homeostasis, yet the impact of specific microbiota communities on osteoimmune response mechanisms is unknown. To discern osteoimmunomodulatory effects imparted by the commensal oral microbiota that are distinct from the systemic microbiota, osteoimmunology studies were performed in both alveolar bone and nonoral skeletal sites of specific-pathogen-free (SPF) vs. germ-free (GF) mice, and SPF mice subjected to saline vs. chlorhexidine oral rinses. SPF vs. GF mice h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 107 publications
0
18
0
Order By: Relevance
“…The oral microbiota induces many immune cells to generate periodontal immune responses due to the highly permeable junctional epithelial attachments on the tooth surface ( 34 ). Therefore, microbial biofilms in healthy individuals can significantly mobilize the periodontal immune microenvironment and mediate the maintenance of periodontal homeostasis ( 35 ). However, the dental follicle structure of the unerupted tooth and the periodontal tissue of the middle part of the incisor is relatively distant from the oral microbial community and show relatively silent immune activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral microbiota induces many immune cells to generate periodontal immune responses due to the highly permeable junctional epithelial attachments on the tooth surface ( 34 ). Therefore, microbial biofilms in healthy individuals can significantly mobilize the periodontal immune microenvironment and mediate the maintenance of periodontal homeostasis ( 35 ). However, the dental follicle structure of the unerupted tooth and the periodontal tissue of the middle part of the incisor is relatively distant from the oral microbial community and show relatively silent immune activities.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is consideration of the unique environment of periodontal tissue and its proximity to oral plaque biofilms. The oral microbiota induces many immune cells to generate periodontal immune responses due to the highly permeable junctional epithelial attachments on the tooth surface (34). Therefore, microbial biofilms in healthy individuals can significantly mobilize the periodontal immune microenvironment and mediate the maintenance of periodontal homeostasis (35).…”
Section: Characteristics Of the Immune Microenvironment In The Dep An...mentioning
confidence: 99%
“…Moreover, SFB in the gut amplifies IL-17 production in a manner dependent on IL-17R signaling within the gut epithelium (37). In contrast, the influence of SFB on oral mucosal immunity is not well described, though a recent study demonstrated that SFB modulates alveolar bone homeostasis in a model of periodontal bone loss (50,82).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, colonization with SFB provoked marked gene expression changes after only 2 days of exposure to fungus. Since SFB is not present in the oral mucosa (28,82), this increased transcriptional landscape is not due to direct bacterial contact with the oral epithelium. Instead, we postulate that SFB in the gut primes distal responses to C. albicans in the oral epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Both MyD88-dependent-TLR and Nod-Like-Receptors are involved in steady-state-hematopoiesis further underscoring the bacterial requirement, and quite likely LPS, for driving the regulation [ 105 ]. Another investigation into the microbial regulation of osteo-immunomodulatory effects suggest the oral microbiome, by selective use of an antibiotic mouthwash, specifically induces the pro-osteoclastic activity in the alveolar bone compartment [ 105 , 106 ]. Together, these studies indicate that specific microbial-niches can modulate disparate immune-functions.…”
Section: Discussionmentioning
confidence: 99%